Layout Design of Copra Factory Facilities in Small and Medium Industry Centers Using Systematic Layout Planning Method - Rio Erwanda (Jurnal Riset Ilmu Teknik, 2023)
This research was conducted on the layout of copra processing facilities. Copra is one of the products to be produced by the Small and Medium Industry Center in the Meranti Islands. The purpose of designing the layout of this copra factory facility is to provide a proposal in the form of a copra processing facility layout with the shortest material handling distance. The methods used in this study are Systematic Layout Planning (SLP) and Arena Simulation. The result of the SLP method is in the form of alternative layout proposals, which will be checked with a simulation model. This Arena simulation is carried out to see whether the production process of the resulting layout is good or not by implementing it into a conceptual model in the Arena software, which is then tested to see the disruptions that exist in the production process, such as the accumulation of raw materials at one of the stations (bottleneck). Based on data processing results, one alternative layout was selected with a material handling distance of 26.33 m from 3 existing alternatives. This selection is based on the smallest material handling distance obtained. Furthermore, testing the layout with the Arena software simulation model found that there was a disruption in the production process in the form of a buildup of raw materials at the smoking and drying station caused by the manual drying process using the scorching heat of the sun so that it takes 4-5 days for the drying process.